Evidence in Civil Law - Hungary - Harsági, Viktória (Law & Society, 2015)
After a brief historical introduction, the short monograph reviews the system of evidence in Hungarian civil proceedings, approaching the topic from the aspect of the basic principles. Following changes in the role of material truth, it presents alterations in the interpretation of and re-interpretation of the notion of the principle of free disposition of the parties. Then it deals with the following basic principles and their relation to evidence: principle of orality, principle of directness, principle of public hearing, principle of equality of arms, right to be heard, ensuring the use of one's mother tongue, principle of procedural economy, the proper (bona fide) conduct of the lawsuit, principle of adversarial hearing, principle of the freedom of proof. After examining the questions of admissibility of evidence and burden of proof, it discusses particular means of evidence, the taking of evidence, the preliminary taking of evidence, costs of evidence, the question of unlawful evidence, and finally, the cross-border taking of evidence.